Upaya Guru Tahfidz dalam Meningkatkan Hafalan Al-Qur’an Siswa Kelas VIII Menggunakan Metode Madinah, Talaqqi, dan Pakistan melalui Program Tahfidz Di SMP Inovatif Al Ibda Soreang - Sinsin Ummu Jahieda; A. Mujahid Rasyid; Fitroh Hayati (Bandung Conference Series: Islamic Education, 2022)
Abstract. Introducing the Qur'an, teaching how to read and memorize it, both in formal and private schools is the responsibility of a teacher. This research is motivated by the existence of students who are less enthusiastic in memorizing the Qur'an, thus hampering the success of the targets that must be achieved in learning tahfidz through the tahfidz program at Al Ibda Innovative Junior High School Soreang. The purpose of this study was to determine: (1) the efforts of the tahfidz teacher in improving the memorization of the Qur'an (2) The steps of learning tahfidz using the Medina, talaqqi, and Pakistani methods (3) The evaluation used by the teacher to determine the improvement of the memorization of the Al-Qur'an. -The Qur'an of class VIII students (4) Weaknesses and advantages of the combined application of the Medina, talaqqi, and Pakistani methods. The researcher used a qualitative descriptive method. The research was conducted at Al Ibda Innovative Junior High School, Soreang. Collecting data in the study using interviews, observation, and documentation. The results of this study are: (1) Teachers must have the ability and understanding of how to become a tahfidz teacher competence. 2) In learning tahfidz, the teacher uses a combined method, namely the Medina, talaqqi, and Pakistani methods. (3) To find out the improvement of students' Al-Qur'an memorization, the teacher looked at the results of the students' memorization test when they entered the Al Ibda Innovative Junior High School Soreang, the progress of learning every three months, and student attendance. (4) The weakness of the application of the combined method is the lack of supporting human resources and the limitation of students who have the ability to exceed the target. The advantage is that it makes it easier for students when memorizing, and with the presence of reading talaqqi, recitations, muroja'ah and ziyyadah will maintain memorization. Abstrak. Mengenalkan Al-Qur’an, mengajari bagaimana membaca dan menghafalnya, baik di sekolah formal maupun swasta sudah menjadi tanggung jawab seorang guru. Penelitian ini dilatarbelakangi oleh masih adanya siswa yang kurang bersemangat dalam menghafal Al-Qur’an, sehingga menghambat pada keberhasilan target yang harus dicapai pada pembelajaran tahfidz melalui program tahfidz di SMP Inovatif Al Ibda Soreang. Tujuan dari penelitian ini, untuk mengetahui: (1) Upaya guru tahfidz dalam meningkatkan hafalan Al-Qur’an (2) Langkah-langkah pembelajaran tahfidz menggunakan metode Madinah, talaqqi, dan Pakistan (3) Evaluasi yang digunakan guru untuk mengetahui peningkatan hafalan Al-Qur’an siswa kelas VIII (4) Faktor kelemahan dan keunggulan penerapan gabungan metode Madinah, talaqqi, dan Pakistan. Peneliti menggunakan metode deskriptif kualitatif. Penelitian dilaksanakan di SMP Inovatif Al Ibda Soreang. Pengumpulan data pada penelitian menggunakan wawancara, observasi, dan dokumentasi. Hasil dari penelitian ini adalah: (1) Guru harus memiliki kemampuan dan pemahaman bagaimana kompetensi menjadi guru tahfidz. 2) Dalam pembelajaran tahfidz, guru menggunakan metode gabungan yaitu metode Madinah, talaqqi, dan Pakistan. (3) Untuk mengetahui peningkatan hafalan Al-Qur’an siswa, guru melihat dari hasil tes hafalan siswa ketika masuk SMP Inovatif Al Ibda Soreang, perkembangan pembelajaran per tiga bulan, dan kehadiran siswa. (4) Adapun kelemahan penerapan penggabungan metode yaitu kurangnya SDM yang mendukung dan adanya pembatasan siswa yang memiliki kemampuan melebihi target. Keunggulannya yaitu memudahkan siswa ketika menghafal, dan dengan adanya talaqqi bacaan, tilawah, muroja’ah dan ziyyadah akan menjaga hafalan.